2020
DOI: 10.3389/fonc.2020.01169
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Early Radiation Associated Cardiac Toxicity Following Neoadjuvant Chemoradiation for Distal Esophageal Cancer

Abstract: This study aimed to prospectively evaluate the early effects of radiation on cardiac structure and function following neoadjuvant chemoradiation for distal esophageal cancer. Conclusions: Our study is the first to our knowledge to prospectively demonstrate radiation associated structural and functional heart damage as early as 3 months following neoadjuvant chemoradiation for distal esophageal cancer. Given the early onset of this subclinical heart damage, strategies should be developed to identify patients at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…2021 ) and sweetened beverages that have been linked to CVD ( Kim et al. 2020 ), radiation therapy that could give rise to a great number of myocardial pathologies ranging from fibrosis to ischemic disease ( Burke et al. 2020 ), and the well-known endocarditis induced by Streptococcal infections ( Chamat-Hedemand et al.…”
Section: Discussionmentioning
confidence: 99%
“…2021 ) and sweetened beverages that have been linked to CVD ( Kim et al. 2020 ), radiation therapy that could give rise to a great number of myocardial pathologies ranging from fibrosis to ischemic disease ( Burke et al. 2020 ), and the well-known endocarditis induced by Streptococcal infections ( Chamat-Hedemand et al.…”
Section: Discussionmentioning
confidence: 99%
“…Patients exposed to radiation with more than 280 mL of V5000 cGy had a 16.8 times more likely chance of developing these cardiac events than those who received a smaller volume ( 192 ). In a prospective study of patients with non-metastatic esophageal cancer, the authors showed that 30% of the patients developed myocardial fibrosis and/or reversible ischemia as early as 3 months following neoadjuvant chemoradiation ( 193 ). Furthermore, several large-scale studies have demonstrated similar findings that chemoradiotherapy increases the risk of cardiotoxicity in lymphoma ( 194 , 195 ) and esophageal cancer treatment ( 196 ) as compared to radiotherapy alone.…”
Section: Synergistic Cardiotoxicities With Chemoradiation or Radioimm...mentioning
confidence: 99%
“…Although MRiPT is still in its infancy, research is currently underway to develop prototype systems for clinical use ( 49 ). In addition to MR-guided daily plan adaptation and PTV margin reduction with consequently better sparing of OARs, MRI may also provide a way to detect subclinical cardiac toxicity after CRT by visualizing areas of myocardial fibrosis and changes in ejection fraction ( 50 ).…”
Section: Rational For Mr-guided Radiotherapy In Esophageal Cancermentioning
confidence: 99%